Influence of additive manufacturing parameters on patient-specific small vessel models based on the neurointerventional simulator HANNES (Transactions on Additive Manufacturing Meets Medicine, 2023)
With the increasing technical development, neuroradiological treatment of diseases in small vessels (diameter of < 2 mm), like arteriovenous malformations, is becoming possible. Endovascular interventions are technically very difficult and require learning and practice in the use of the instruments. There is a great need for in-vitro training simulators to avoid inappropriate animal experiments. This article describes the analysis of influencing parameters additively manufactured patient specific small vessel models based on the existing neurointerventional simulator HANNES and an established workflow for the fabrication of vessel models. Many printing parameters during the design or fabrication of the model may have an influence on the small complex hollow structures. In this article, a selection of parameters of the stereolithography process and their possible influence are explained in more detail. Subsequently, the findings should be investigated in a printing study for a more detailed analysis of the parameters.AcknowledgmentsThe authors would like to thank the Federal Ministry of Education and Research – BMBF for funding the project MONTYPIE (FKZ: 16LW0301K).Author's StatementThe project is funded by BMBF. The authors state no conflict of interest. Consent was obtained from all persons involved in this study.
Keywords: Additive Manufacturig; medical training; endovascular intervention; 3D modeling; process parameters